Tiffany Trotter: capstone - Trotter, Tiffany, artist (Colorado State University. Libraries, 2015)
The artist's statement: In my first semester capstone Painting course I began to explore issues surrounding climate change and global sustainability. As I explored these issues I found myself increasingly concerned with the conditions of endangered animal species. In my pieces, partially inspired by folk art and museum diagrams, I painted a number of endangered arctic species in a desert environment where they could not survive. With this work and another from my first semester capstone, I hoped to highlight the connection between the species and their habitat. The survival of these animals depends on the continued existence of their habitats. Moving into my final capstone course my focus remained on endangered animal species though I decided to address the subject in another way. Rather than highlighting the connection between animals and their habitats I focused on the beauty and uniqueness of each specific species. My goal is that by shifting the focus to the individuality of the species the viewer feels a greater sense of ownership to the plight of endangered animals. In my series, At Risk, I painted seven pieces; each of different endangered or critically endangered species. In each work I focused on emphasizing a unique visual characteristic of the species. In Reticulated Flatwoods Salamander, for example, I concentrated on highlighting its engaging form and pattern. In this series of work, I hope to create a personal and intimate connection between animal and viewer.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting